2016
DOI: 10.1159/000441457
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Peripheral Depression Biomarkers

Abstract: Background: To aid in the differentiation of individuals with major depressive disorder (MDD) from healthy controls, numerous peripheral biomarkers have been proposed. To date, no comprehensive evaluation of the existence of bias favoring the publication of significant results or inflating effect sizes has been conducted. Methods: Here, we performed a comprehensive review of meta-analyses of peripheral nongenetic biomarkers that could discriminate individuals with MDD from nondepressed controls. PubMed/MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
1
34
1
1
Order By: Relevance
“…However, in most cases, the sample size of component studies was small, or the P ‐value was close to the nominal significance threshold. Similar findings were observed in umbrella reviews on peripheral biomarkers for depression and bipolar disorder .…”
Section: Discussionmentioning
confidence: 86%
“…However, in most cases, the sample size of component studies was small, or the P ‐value was close to the nominal significance threshold. Similar findings were observed in umbrella reviews on peripheral biomarkers for depression and bipolar disorder .…”
Section: Discussionmentioning
confidence: 86%
“…Here studies have shown that glucocorticoids are increased in depression (Barden, 2004;Charney & Manji, 2004;Gold et al, 2002), anxiety (Yoon & Joormann, 2012), schizophrenia (Berger et al, 2016), bipolar disorder (Belvederi Murri et al, 2016, although they are decreased in PTSD (Yehuda et al, 2005 #5143)), conduct disorders (Buydens-Branchey & Branchey, 2004;Pajer et al, 2001) and burnout (Pruessner et al, 1999). This high discrepancy of data has been related to various factors, ranging from publication bias (Carvalho et al, 2016), changes in glucocorticoid receptors' regulation (Yehuda et al, 2006) and adaptation mechanisms to chronic stress (Miller et al, 2007).…”
Section: Implications Of the Dsm5/rdoc Debate For Human Stress Researchmentioning
confidence: 91%
“…Considering that no single biomarker will probably define any psychiatric disorder as defined by traditional diagnostic boundaries [13, 20, 21], it will be essential to pursue in parallel theory- and data-driven discovery approaches to delineate the multivariate and combinatorial profiles of biomarkers (across units of analysis) that account for the heterogeneity of mental illnesses as they manifest clinically.…”
Section: The Convergence Of Different Fieldsmentioning
confidence: 99%